Aging, not Parkinson’s disease, decreases a recalibration of body ownership caused by vision-respiratory interaction - Shoji, Daiki; Honma, Motoyasu; Masaoka, Yuri; Nakayama, Momoka; Kosuge, Miku; Kosuge, Shota; Uchida, Yuki; Sakakura, Shunsuke; Matsui, Misako; Ito, Naohito; Nohara, Tetsuhito; Watanabe, Daishi; et al. (Frontiers in Physiology, 2024)
Recalibration of body ownership perception occurs through an integration among multiple modalities. A recent study has shown that respiratory rhythm also causes the recalibration of ownership perception. However, the risk factors influencing the recalibration of ownership perception caused by vision-respiratory interaction remain unclear. In this study, focusing on aging and Parkinson's disease (PD), we examined the effects of those risk factors on the recalibration. By applying the rubber hand illusion (RHI), which temporarily alters ownership perception, and using a device that synchronizes the respiratory rhythm with the movement of a mannequin hand, we measured a change in ownership perception in RHI training by visionrespiratory interaction. The changed ownership was compared among the elderly healthy, PD, and young healthy groups. The results showed no difference in the changed ownership between the elderly healthy and PD groups, while the two groups decreased the change in the ownership perception than the young healthy group. The finding suggests that aging, not PD, related to the recalibration of ownership perception by vision-respiratory interaction.